TEACHER’S SELF CONFIDENCE IN EVALUATION OF ONLINE LEARNING AT THE STATE’S FIRST MIDDLE SCHOOL 39 SAMARINDA - Normayani, Normayani; Suryaningsi, Suryaningsi (Unmul Civic Education Journal, 2022)
This study aims to find out about the teacher's self-confidence in evaluating online learning at SMP Negeri 39 Samarinda on the teacher's efforts to increase self-confidence in evaluating online learning at SMP Negeri 39 Samarinda, as well as factors that support teacher confidence in providing evaluations of online learning at SMP Negeri 39 Samarinda, and to find out the factors that hinder teachers in providing learning evaluations at SMP Negeri 39 Samarinda. The type of research is descriptive qualitative research with a focus on the teacher's efforts to increase self-confidence in evaluating online learning at SMP Negeri 39 Samarinda, as well as factors that support teachers' self-confidence in providing evaluations of online learning at SMP Negeri 39 Samarinda, and to find out factors that hinder teachers in providing learning evaluations at SMP Negeri 39 Samarinda. Sources of research data are sourced from primary and secondary data, with data collection methods are through observation, interviews, and documentation. Data analysis techniques through data collection, presentation and conclusion. The results showed that the teacher's self-confidence in evaluating online learning at SMP Negeri 39 Samarinda was through the results of the study showing the teacher's efforts to increase self-confidence in evaluating online learning at SMP Negeri 39 Samarinda through cognitive, motivational, affective, and selection processes. The factors that support teachers' self-confidence in providing evaluations of online learning at SMP Negeri 39 Samarinda are the support provided by teachers, schools and the community (parents of students. The inhibiting factors for teachers in evaluating online learning at SMP Negeri 39 Samarinda, The obstacle comes from the internal side, namely the school and externally comes from the parents.